Triglyceride-glucose index linked to all-cause mortality in critically ill patients: a cohort of 3026 patients - Ying Liao; Rongting Zhang; Shanshan Shi; Yukun Zhao; Yibo He; Lihua Liao; Xueqin Lin; Qian Guo; Yani Wang; Liling Chen; Weiguo Li; Shihai Li; et al. (Cardiovascular Diabetology, 2022)
Abstract Background Triglyceride-glucose (TyG) index as a reliable surrogate of insulin resistance (IR) has been shown to be related to adverse clinical outcomes in patients with acute coronary syndrome, heart failure, ischemic stroke and so on. However, the relationship between TyG index and all-cause mortality in intensive care unit (ICU) patients remains unknown. The purpose of this study was to investigate the correlation between TyG index and all-cause mortality to evaluate the impact of IR on the prognosis of this population. Methods This was a retrospective observational study that included 3026 patients who had an initial triglyceride and glucose data on the first day of ICU admission, and all data were extracted from the Medical Information Mart for Intensive Care III (MIMIC-III) database. These patients were grouped into quartiles (Q1–Q4) according to TyG index. The Kaplan–Meier analysis was used to compare all-cause mortality among the above four groups. Cox proportional hazards analyses were performed to examine the association between TyG index and all-cause mortality. Results During 10.46 years of follow-up, 1148 (37.9%) patients died, of which 350 (11.6%) occurred during the hospital stay and 258 (8.5%) occurred during the ICU stay. Kaplan–Meier analysis showed that the risk of all-cause mortality was significantly higher in patients with higher TyG index (log-rank P = 0.021). Multivariable Cox proportional hazards analyses showed that the TyG index was an independent risk predictor of ICU death (HR: 1.72, 95% CI 1.18–2.52, P = 0.005) and hospital death (HR: 2.19, 95% CI 1.59–3.03, P < 0.001), and each 1-unit increased in the TyG index, a 1.19-fold increase in the risk of death during the hospital stay. Conclusions TyG index is strongly related to the all-cause mortality increasing in critically ill patients. This finding indicates that the TyG index might be useful in identifying people at high risk of ICU death and hospital death.